Power and Hierarchy Relationships in a Local Productive Arrangement of a Brazilian City - Mello, José André Villas Boas; Pinto, Bruno Guimarães Jorge (Revista Geográfica de América Central., 2022)
This research aims to identify how power and hierarchy relations emerge in a production system that influence the authenticity dimensions of a local productive arrangement. The research is exploratory and had data collected from interviews with local managers from organizations of local size and influence. The data collected from the interviews allowed qualifying the studied productive system, as well as advancing on Storper and Harrison’s (1991) proposals, taking as original the study of a local productive arrangement (LPA) of a medium and peripheral city in Brazil. It is concluded that the qualitative aspects favorable to the LPA have the “core-ring structure with coordinating signature” as a very present characteristic that influences the authenticity dimensions of the arrangement. Given this perspective, it is also highlighted that the territorial dimension and rootedness are well defined, as the region is perceived as the best option for the purchase and installation of automotive businesses. Tacit knowledge, innovation, and governance are underdeveloped. As a central result, one can point to a possible stronger variable to what Lastres and Cassiolato (2004) call the authenticity of local productive arrangements, that is, the relations of power and hierarchy existing in the production system can constitute a variable that interferes in the other dimensions and confers the authenticity of a local productive arrangement.